Nutritional interventions to improve sleep in team-sport athletes: A narrative review - Gratwicke, M.; Miles, K. H.; Pyne, D. B.; Pumpa, K. L.; Clark, B. (Nutrients, 2021)
Athletes often experience sleep disturbances and poor sleep as a consequence of extended travel, the timing of training and competition (i.e., early morning or evening), and muscle soreness. Nutrition plays a vital role in sports performance and recovery, and a variety of foods, beverages, and supplements purportedly have the capacity to improve sleep quality and quantity. Here, we review and discuss relevant studies regarding nutrition, foods, supplements, and beverages that may improve sleep quality and quantity. Our narrative review was supported by a semi-systematic approach to article searching, and specific inclusion and exclusion criteria, such that articles reviewed were relevant to athletes and sporting environments. Six databases—PubMed, Scopus, CINAHL, EMBASE, SPORTDiscus, and Google Scholar—were searched for initial studies of interest from inception to November 2020. Given the paucity of sleep nutrition research in the athlete population, we expanded our inclusion criteria to include studies that reported the outcomes of nutritional interventions to improve sleep in otherwise healthy adults. Carbohydrate ingestion to improve sleep parameters is inconclusive, although high glycemic index foods appear to have small benefits. Tart cherry juice can promote sleep quantity, herbal supplements can enhance sleep quality, while kiwifruit and protein interventions have been shown to improve both sleep quality and quantity. Nutritional interventions are an effective way to improve sleep quality and quantity, although further research is needed to determine the appropriate dose, source, and timing in relation to training, travel, and competition requirements.